Fight Club - Chuck Palahniuk (New York W. W. Norton, 1996)
The first rule about fight club is you don't talk about fight club.Chuck Palahniuk's outrageous and startling debut novel that exploded American literature and spawned a movement. Every weekend, in the basements and parking lots of bars across the country, young men with white-collar jobs and failed lives take off their shoes and shirts and fight each other barehanded just as long as they have to. Then they go back to those jobs with blackened eyes and loosened teeth and the sense that they can handle anything. Fight club is the invention of Tyler Durden, projectionist, waiter, and dark, anarchic genius, and it's only the beginning of his plans for violent revenge on an empty consumer-culture world.
Keywords: Fiction; Adult; Classics; Thriller